The Organizational learning and its impact on the quality of creative performance - Ahmed Al-Salim, Ahmed Abdul Salam; Jawad, Shawqi Naji (International Journal of Scientific Research and Management (IJSRM), 2018)
This study was based on the descriptive analytical method, which was a group of companies producing medicines in all of Iraq, which number up to the preparation of the study (18) companies, The sample of the study was taken from these companies in a simple random sample (12) companies. The sampling unit consisted of the assistance of the general managers of the company and the heads of the departments. The number of them was (78). The study found a set of results of which, there is a statistically significant effect of organizational learning on the quality of the creative performance of staff to general managers and heads department. Based on the findings of the study were presented a set of recommendations was the most prominent, the medicine manufacturers to adopt modern management concepts, especially organizational learning to become able to adapt and harmony with the environmental challenges. To overcome difficulties in front of the heads of departments and provide information and sources of knowledge ample to enable them to achieve creative performance